(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to investigate the impact of artificial intelligence, with its dimensions (genetic algorithms, intelligent agents, expert systems), on managerial decision-making, with its aspects (decision-making stages, decision-making determinants, decision-making elements, participation in decision-making) in Saudi Telecommunications Company. To achieve the study objectives, a descriptive-analytical approach was followed. The study population included all employees within Saudi Telecommunications Company. Due to the difficulty of conducting a comprehensive census of all individuals in the study population, the study used a simple random sampling method by distributing the questionnaire link across all social media platforms used by the study population. The study sample comprised 464 individuals who responded to the questionnaire. The study results revealed a statistically significant positive impact of the level of artificial intelligence usage on managerial decision-making in Saudi Telecommunications Company. A strong positive correlation was found between the usage of artificial intelligence and managerial decision-making in the company. The study recommended focusing on providing financial resources, logistical capabilities, and support for the development of artificial intelligence applications that can help maintain the outstanding level of artificial intelligence application usage in Saudi Telecommunications Company. Additionally, efforts should be directed towards providing the technological infrastructure that contributes to enhancing the company’s ability to utilize artificial intelligence applications.